2017
DOI: 10.1007/s11920-017-0861-z
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on Recent Research Into Animal-Assisted Interventions in the Military and Beyond

Abstract: With regard to AAI within the military, several canine interaction programs have been utilized to assist service members in coping with various issues. Therapy dogs have been deployed with Combat-Operational Stress Control units; they have been integrated into medical clinics and behavioral health treatment programs in garrison; and policy has been developed to address the use of therapy animals in military treatment facilities. General research in AAI has demonstrated efficacy for certain presenting issues (s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Additionally, much of the extant literature to date has focused on the beneficial health effects of HAI through long-term pet ownership rather than the effects of specific interventions. Finally, reviews of HAI specifically related to therapeutic interventions or specific clinical populations suggest an overall lack of methodological rigor [16, 18–20] which is a considerable barrier to progress in the field. The current study team noted these trends when designing the trial and decidedly erred on the conservative side in relation to specifying the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, much of the extant literature to date has focused on the beneficial health effects of HAI through long-term pet ownership rather than the effects of specific interventions. Finally, reviews of HAI specifically related to therapeutic interventions or specific clinical populations suggest an overall lack of methodological rigor [16, 18–20] which is a considerable barrier to progress in the field. The current study team noted these trends when designing the trial and decidedly erred on the conservative side in relation to specifying the control group.…”
Section: Discussionmentioning
confidence: 99%
“…HAI refers to the purposeful and semistructured social pairing of a human with a domesticated animal for therapeutic purposes. A number of diverse studies have found that HAI can have positive effects on emotional and physical functioning, stress reactivity, and social functioning [16–18]; and among those with psychiatric symptoms, HAI interventions have been found to improve depression, anxiety, and PTSD [16, 19, 20]. Although promising, the HAI literature is tempered by methodological limitations, such as difficult-to-replicate study procedures, over-reliance on self-report measures, and lack of adequate controls/randomization (e.g., [18–20]).…”
Section: Introductionmentioning
confidence: 99%